2020
DOI: 10.4103/jcd.jcd_223_20
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of push-out bond strength of BioRoot RCS and AH Plus after using different irrigants: An in vitro study

Abstract: Aim: The aim of this study was to compare push-out bond strength of root canal spaces filled with AH-Plus and BioRoot RCS after using different irrigants. Materials and Methods: Eighty single-rooted teeth were decoronated and endodontically treated by crown-down technique using ProTaper Universal rotary files progressively till F4 (40/0.06). Samples were divided into two groups according to the sealer ( n = 40): Group A = BioRoot RCS, Group B … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 17 publications
(21 reference statements)
2
3
0
Order By: Relevance
“…The results of the current study were in agreement with previous studies (51,52) , which reported that the EDTA-GT group produced lower PBS values compared to EDTA group. However, the results were not statistically significant.…”
Section: Discussionsupporting
confidence: 93%
“…The results of the current study were in agreement with previous studies (51,52) , which reported that the EDTA-GT group produced lower PBS values compared to EDTA group. However, the results were not statistically significant.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, AH Plus appeared to contract during setting [ 36 ]. This finding was in accordance with several other studies that evaluated the impact of the presence or absence of a smear layer [ 17 ] or of using different dentin conditioning [ 37 ] and irrigation protocols [ 38 ] on the POBS of BioRoot RCS, which was better than that of AH Plus sealer.…”
Section: Discussionsupporting
confidence: 92%
“…Being resin free, it is capable of flowing into the dentinal tubules with no shrinkage and provides excellent adhesion to dentin and gutta-percha and its ability to seal auxiliary canals. [ 15 ] A study done by Dayanand Chole et al . [ 3 ] reported that BioRoot RCS showed the highest bond strength than AH Plus and MTA Fillapex due to its true self-adhesive nature.…”
Section: Discussionmentioning
confidence: 99%